Coupling Effects of Nitrogen and Irrigation Levels on Growth Attributes, Nitrogen Use Efficiency, and Economics of Cotton - Kumar, Rakesh; Pareek, Narendra Kumar; Kumar, Uttam; Javed, Talha; Al-Huqail, Asma A.; Rathore, Vijay Singh; Nangia, Vinay; Choudhary, Ashok; Nanda, Gangadhar; Ali, Hayssam M.; Siddiqui, Manzer H.; Youesf, Ahmed F.; et al. (Frontiers in Plant Science, 2022)
Nitrogen (N) fertilization plays a pivotal role in physio-morphological attributes and yield formation of field-grown cotton (Gossypium hirsutum L.), but little is known of its interaction with irrigation levels. Therefore, the current study was conducted with objective of evaluating the impact of irrigation and nitrogen levels on growth attributes and nitrogen use efficiency of Bt Cotton (Gossypium spp.) in the hot arid region. The experiment consisted of a factorial arrangement of three irrigation levels (200, 400, and 600 mm) and four nitrogen rates (0, 75, 150, and 225 kg ha-1), in a split plot design with three replications. Nitrogen fertilization and irrigation levels influenced cotton growth attributes and yield. The highest leaf area index, dry matter accumulation, crop growth rate, and relative growth rate were achieved at 225 kg N ha-1 and irrigation level 600 mm as compared to other experimental treatments. Similarly, nitrogen uptake and content by seed, lint and stalk and total nitrogen uptake recorded maximum at 225 kg N ha-1 and irrigation level 600 mm. Interestingly, the treatment 600 mm of irrigation and 150 kg N ha-1 displayed significant increase in nitrogen use efficiency indices such as agronomic efficiency of nitrogen (AEN), and recovery efficiency of nitrogen (REN) while partial factor productivity of nitrogen (PFPN) and internal nitrogen use efficiency (iNUE) were significantly higher with application of 600 mm of irrigation and nitrogen application rate of 75 kg ha-1. Application of 600 mm of irrigation along with 225 kg N ha-1 resulted in significant increase in gross return, net return and B:C ratio than any other treatment combinations. So, application of 600 mm of irrigation along with 225 kg N ha-1 could be recommended for achieving higher growth and yield as well as profitability of Bt Cotton under hot arid region of Rajasthan and similar agro-ecologies.